Vitamin D and Bronchial Asthma: An overview of the last five years - Hall, Sannette C. (Clin Ther, 2017)
Vitamin D is a potent immunomodulator capable of dampening inflammatory signals in several cell types involved in the asthmatic response. Its deficiency has been associated with increased inflammation, exacerbations and overall worse outcomes in patients with asthma. Given the increase in the prevalence of asthma over the last few decades, there has been enormous interest in the use of vitamin D supplementation as a potential therapeutic option. Several studies have found that low serum levels of vitamin D (< 20 ng/ml) are associated with increased exacerbations, increased airway inflammation, decreased lung function and poor prognosis in asthmatic patients. Results from the in vitro and in vivo studies in animals and human have suggested that supplementation with vitamin D can ameliorate several hallmark features of asthma. However, the findings obtained from clinical trials are controversial and do not unequivocally support the beneficial role of vitamin D in asthma. Largely, interventional studies in children, pregnant women and adults have primarily found little-to-no effect of vitamin D supplementation on improved asthma symptoms, onset or progression of the disease. This could be related to the severity of the disease process and other confounding factors. Despite the conflicting data obtained from clinical trials, vitamin D deficiency does influence the inflammatory response in the airways. Further studies are needed to determine the exact mechanisms by which vitamin D supplementation may induce anti-inflammatory effects. Here, we critically reviewed the most recent findings from in vitro studies, animal models, and clinical trials regarding the role of vitamin D in bronchial asthma.